The Effect of Health Care Quality Town Patient Satisfaction in Indonesia - Nanik Sulistyorini; Sutopo Patria Jati; Farid Agushybana (Universitas Aisyah Pringsewu, 2021)
The quality of health services can be measured using standard criteria starting from the aspects of the structure, process and results of a health service institution. In addition, the quality of health services is also related to patient satisfaction where patient satisfaction is a measure of the success of the quality of health services, while patient dissatisfaction will be a problem that needs to be considered in improving the quality of health services. The purpose of this article is to analyze the quality of health services as a form of hospital management commitment in increasing patient satisfaction in Indonesian hospitals which was compiled using the literature study method. Articles were selected based on inclusion criteria and keywords through the Google Scholar database, Sinta indexed journals and international journals, and 13 main articles were found to be studied. The results of this study found that the health services provided by hospitals in Indonesia had a significant effect on patient satisfaction. , and has a positive effect on patient behavior and loyalty. In addition, in general the quality of health services has a good category and patient satisfaction in the inpatient unit. The conclusion of this study is that the quality of hospital services can positively affect patient satisfaction. In addition, the quality of health services can be seen from reliability, responsiveness, assurance, empathy, and tangible. Better service quality is very important for every organization, especially in health organizations, especially in health services.